PENINGKATAN KUALITAS PEMBELAJARAN PENDIDIKAN KEWARGANEGA RAAN STANDAR KOMPETENSI MENAMPILKAN PARTISIPASI DALAM USAHA PEMBELAAN NEGARA DENGAN METODE PEMBELAJARAN KOOPERATIFMODEL JIGSAWBERBASIS TUTOR SEBAYA PADA SMP NEGERI 1 TAMBAKROMO PATI - NGASIBAN, NGASIBAN (2011)
This study aimed to describe the increasing quality of the learning process and describe the increasing quality of the learning outcomes of subjects Citizenship Education through the jigsaw model of cooperative learning methods based on peer tutor students in grade IX SMP 1 Tambakromo. This study is a class action, namely research conducted in the classroom with emphasis on perfecting and improving learning. Location of the study in class IX A Junior Secondary School 1 Tambakromo Starch school year 2010/2011, amounting to 32 students. The experiment was conducted in two cycles, each cycle consisting of four stages, namely planning, action, observation, and reflection. Results of reflection is used as the basis for subsequent action plan. Data collection techniques used were participant observation, depth interviews, field notes, triangulation and tests. Data analysis techniques to determine the interaction between the components of the learning process quality improvement. While improving the quality of learning outcomes by increasing absorption and completeness classical data analysis technique was used achievement test results. The average percentage increase in the quality of the process of pre cycle to the cycle I of 36.2%. The average percentage increase from cycle I to cycle II of 14.1%. The average percentage increase from pre cycle to cycle II of 50.3%. As for the quality of learning outcomes, the average value of 71.4 pre cycle increased to 73.6 in the first cycle and increased again to 77 on the second cycle. Classical completeness also increased from 56% in pre cycle, then 72% in the first cycle and finally 88% in cycle II. In addition, internal factors namely motivation, interest, attention, self-confidence and external factors namely teachers, learning resources, peer support increased quality of learning through cooperative learning methods jigsaw model-based peer tutors.